2021
DOI: 10.1039/d1ta01147b
|View full text |Cite
|
Sign up to set email alerts
|

Highly stable titanium–manganese single flow batteries for stationary energy storage

Abstract: Manganese-based flow batteries have attracted increasing interest due to their advantage of low cost and high energy density. However, the sediment (MnO2) from Mn3+ disproportionation reaction creates the risk to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…As the current density increases, the EE and VE of the full cell decrease. However, at a current density of 20 mA cm –2 , the VE and EE are as high as 94.2 and 91.4%, respectively, which are highly comparable to those of the redox flow batteries (Figure d). , Impressively, it is shown that the CEs of the full cell are >99% at all rates (Figure e). In addition, to show the practical applications of the aqueous static MnO 2 –Cr (Bi) batteries, we demonstrated our device to be able to power an LED digital screen with a symbol of “USTC” (Figure f).…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…As the current density increases, the EE and VE of the full cell decrease. However, at a current density of 20 mA cm –2 , the VE and EE are as high as 94.2 and 91.4%, respectively, which are highly comparable to those of the redox flow batteries (Figure d). , Impressively, it is shown that the CEs of the full cell are >99% at all rates (Figure e). In addition, to show the practical applications of the aqueous static MnO 2 –Cr (Bi) batteries, we demonstrated our device to be able to power an LED digital screen with a symbol of “USTC” (Figure f).…”
mentioning
confidence: 66%
“…The excessive demands of renewable energy sources have urged the development of advanced electrochemical energy storage (EES) systems, which are considered to be the most promising energy storage technologies for large-scale applications. However, the existing EES technologies, as represented by lithium-ion batteries, have been hindered by their safety concerns in recent years due to the utilization of flammable, volatile, and toxic organic electrolytes. Therefore, much effort has been dedicated to the exploration of aqueous rechargeable batteries. Among them, aqueous MnO 2 -based batteries (AMBs) are excellent alternatives, especially in large-scale energy storage applications, ,, owing to their high rate, environmental benignity, fabrication easiness, long cycle life, and high safety. …”
mentioning
confidence: 99%
See 3 more Smart Citations